Intercultural constructions of the New Testament: Epistemological foundations - Loba-Mkole, Jean-Claude (HTS teologiese studies, 2021)
The present study discusses epistemological foundations of intercultural constructions of the New Testament in Africa. Before embarking on this discussion, it documents the history and procedures of this interpretive tool. In Africa, the intercultural method emanates from the paradigm of inculturation coupled with reconstruction. It has already embraced biblical exegesis, translation studies, canonical criticism and ecological hermeneutics.Contribution: The insights of the article ‘Intercultural constructions of the New Testament: Epistemological foundations’ pertain firstly to the description of the method of intercultural constructions, taking stock of its emergence, development, procedures, and epistemological foundations in both African and international theological circles. Secondly, the study has specifically established the following epistemological foundations of the intercultural method: interculturality as the cradle of the New Testament corpus, an existential mode, an interpretive paradigm, and interaction with a triple hexagonal dimension. The latter includes a triple pitfall (to avoid), a triple frame of reference, a triple epistemological privilege, a triple epistemological value, a triple ethical value, and a triple cultural position.